Imigração e colonização alemã no Vale do Taquari/RS: as descontinuidades e as continuidades do processo de identificação territorial - Franz, Juliana Cristina (2020)
In the context of Cultural Geography, the present study contemplates the local and regional scale as a focus of analysis, focusing on the process of German immigration and colonization in the central region of Vale do Taquari/RS. Since the beginning of the migratory process, immigrants have faced the need to adapt their knowledge, practices to the new land, adding previously unknown values, shaping the processes of reconstruction of their identity. The interrelationships responsible for the spatial reorganization of the Vale do Taquari in contemporary times are also considered. The research problem proposed in this thesis is to understand the contradictory and combined processes, the continuities (permanencies) and, at the same time, the discontinuities (ruptures in the socio-cultural characteristics present in the territorial identity of the immigrants and descendants of German colonists, which are currently being reproduced in the Vale do Taquari. Then, the general objective of the thesis is to understand the processes of territorial identification based on the contributions of German immigration and colonization mediated by the contradictory and combined processes of maintenance and loss of socio-cultural characteristics currently present in the Vale do Taquari/RS. The methodological path followed was the qualitative one, with the use of quantitative data to grasp the local and regional reality. In the literature review, the concepts of territory, territoriality, culture, identity and cultural codes were discussed and reinterpreted, seeking historical references about the process of German immigration and colonization in order to link this process to the conceptual basis. From the regionalization carried out, the research deepened the understanding of the territorial clipping, identifying where the German colonization was denser in the Vale do Taquari, that is, in the central region, since it is where there is a significant presence of German immigrants from the second half of the nineteenth century and onwards. The qualitative orientation of the methodology was operationalized through interviews with representatives of the municipal government and members of local communities. The regional cultural and territorial reality is identified from the cultural codes of language, architecture, festivities, gastronomy, popular culture and religion. Thus, by approaching the conceptualization of culture with the object of study of this thesis, it is understood that culture is intrinsic to the territorial relations established by German immigrants and their descendants in the territorial framework of study. This inseparability can be perceived by the constructed territorialities and the process of cultural and territorial identification. Moreover, with the tendency of cultural homogenization given by globalization, there is also a valorization of difference, that is, of alterity, and sometimes a commodification of ethnic-cultural codes. There is a new interest in the local, in which globalization itself exploits this differentiation, establishing a new articulation between the global and the local. In this context, the place should no longer be confused with old identities firmly rooted in well-defined localities; but instead the place is steeped in the logic of globalization. Globalization is likely to produce new global and local identifications at the same time instead of destroying national identities. This situation leads to the appreciation of local peculiarities and/or singularities, mainly encouraging tourism, and, consequently, may be one of the strategies for the local and regional development of the territorial units that make up the Vale do Taquari region.